Tingkat Kehilangan Air Minum Perumda Air Minum Kota Palangka Raya dengan Neraca Air Wb-Easycalc dan Infrastructure Leakage Indeks (ILI) - Niam Bawa Waskita; Eddy Setiadi Soedjono (LPPM Institut Pendidikan Nusantara Global, 2026)
As the entity responsible for managing the drinking water supply system in Palangka Raya City, Perumda Air Minum Kota Palangka Raya faces a critical challenge in addressing the high level of water losses. In 2022, the company reported a Non-Revenue Water (NRW) level of 49.81%. This figure substantially exceeds the national reduction target of 20%, thereby necessitating immediate intervention measures.The primary objective of this study is to conduct a comprehensive analysis of the Water Balance and to evaluate the Infrastructure Leakage Index (ILI), with the aim of providing recommendations and assessing the effectiveness of the water loss control programs implemented by Perumda Air Minum Kota Palangka Raya. The research methodology employs data analysis using the WB-EasyCalc application to derive NRW and ILI values. In 2023, the total distributed water volume was recorded at 5,593,863 m³, of which 2,807,589 m³ was billable. Based on the Water Balance calculation, the annual water loss amounted to 2,786,274 m³, equivalent to 49.81%. The ILI assessment yielded a value of 26.97, with an average daily pressure of 9.7 meters. This score places the utility within Category D, indicating severe inefficiency and excessive resource wastage, thus requiring urgent corrective measures. Recommendations for water loss control emphasize the need for systematic evaluation and enhancement of existing programs. Priority improvements include the establishment of District Metered Areas (DMA), the implementation of customer meter surveys and calibrations, and the strengthening of pressure management practices.